2018
DOI: 10.1136/heartjnl-2018-313397
|View full text |Cite
|
Sign up to set email alerts
|

Chronic heart failure management and remote haemodynamic monitoring

Abstract: Heart failure (HF) has a large societal and economic burden and is expected to increase in magnitude and complexity over the ensuing years. A number of telemonitoring strategies exploring remote monitoring and management of clinical signs and symptoms of congestion in HF have had equivocal results. Early studies of remote haemodynamic monitoring showed promise, but issues with device integrity and implantation-associated adverse events hindered progress. Nonetheless, these early studies established that haemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…HF is characterized by complex therapeutic regimens, frequent hospitalizations, and a poor prognosis, resulting in a tremendous health care burden [3]. In certain instances, these issues are also fundamental targets of a strategy for HF prevention and treatment [4,5]. It is crucial to discriminate accurately among patients with HF to identify those who have a high risk of in-hospital mortality and readmission, as well as to guide the use of different therapies based on patients' features.…”
Section: Introductionmentioning
confidence: 99%
“…HF is characterized by complex therapeutic regimens, frequent hospitalizations, and a poor prognosis, resulting in a tremendous health care burden [3]. In certain instances, these issues are also fundamental targets of a strategy for HF prevention and treatment [4,5]. It is crucial to discriminate accurately among patients with HF to identify those who have a high risk of in-hospital mortality and readmission, as well as to guide the use of different therapies based on patients' features.…”
Section: Introductionmentioning
confidence: 99%
“…A study (21) has shown that Iva could inhibit the oxidative stress reaction of myocardial cells in CHF rats, and another study (22) also showed that trimetazidine, as a new anti-myocardial ischemia drug, also had the function of oxygen free radical inhibition, oxidation resistance and apoptosis, which partially explained the changes in SOD expression in our conclusion. It was considered that (23) TGF-β1, a multifunctional regulatory factor, could affect MF through Smads-dependent and Smads-independent pathways. There is also a study (24) showing that excessive synthesis and deposition of COL-I promoted MF in patients with hypertension and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The leading concept behind these intra-cardiac devices for HF monitoring is that cardiac filling pressure increases days to weeks before overt clinical exacerbation occurs [ 86 , 87 ]. Several technologies were developed over the past decade in order to accurately measure pressure at different sites along the cardiac circulation and transmit this information to a care facility, where care-givers can appropriately react by changing the treatment dose and strategy [ 87 , 88 ].…”
Section: Implantable Devices To Monitor Heart Failure (Hf) Hemodynmentioning
confidence: 99%